The Role of Islamic Religious Education in Shaping Students' Spiritual Resilience in the Digital Era - Putri Hilda Mavaza; Fitriah M Suud (Education and Sociedad Journal, 2026)
Islamic Religious Education in higher education plays an important role in shaping students' spiritual resilience in the midst of the challenges of the digital era which is marked by psychological pressure, decreased mental well-being, and weakening of religious identity. This research aims to explore the role of PAI in forming the spiritual resilience of PAI Study Program students. The study used a qualitative approach with a phenomenological design through semi-structured in-depth interviews with nine participants consisting of students and lecturers selected by purposive sampling. Data analysis was carried out using Interpretative Phenomenological Analysis (IPA). The results of the study show that effective PAI learning strategies are contextual, participatory, reflective, and integrated with digital technology based on student-centered learning. Students' spiritual resilience develops through strong faith, the practice of worship as an adaptive coping mechanism, and the ability to interpret life's difficulties positively (positive meaning-making). The impact of PAI learning can be seen at three interrelated levels: increased psychological calmness, consistency of worship, and the ability to interpret exams as a process of faith growth. These findings provide practical implications for the development of a more integrative PAI curriculum between cognitive, affective, and spiritual dimensions in responding to the challenges of the digital era.